The potential role of direct and indirect bronchial challenge testing to identify overtreatment of community managed asthma. Issue 10 (October 2014) - Manoharan, A.; Lipworth, B. J.; Craig, E.; Jackson, C.
Summary Background Although airway hyperresponsiveness (AHR) is a defining feature of asthma pathophysiology, bronchial challenge testing is not routinely used in primary care asthma management. Objective The aim of this study was to evaluate the potential role of direct (methacholine) and indirect (mannitol) challenge testing in community managed asthma. Methods Patients currently treated for asthma from Tayside and Fife were identified by the Health Informatics Centre (HIC) and invited to take part in the study. At screening, the following tests were carried out: spirometry, methacholine and mannitol challenge, exhaled nitric oxide (FeNO); Asthma Control Questionnaire (ACQ) and Mini Asthma Quality of Life Questionnaire (AQLQ). Results A total of 3388 asthmatics were initially identified by HIC with 423 positive responses and 123 completing the study. Seventy percent had either a positive methacholine (PC20 < 8 mg/mL) or mannitol challenge (PD15 < 635 mg), and 30% were non‐responsive to both challenges. Fourteen percent of methacholine responders (n = 74) were negative to mannitol, and 16% of mannitol responders (n = 76) were negative to methacholine. Spirometry, FeNO, ACQ and AQLQ were significantly better in the non‐responder group who were exposed to high‐dose inhaled corticosteroids and frequent long‐acting beta‐agonists. Conclusions and Clinical Relevance We found that 30% of unselected patients with community managed asthma were challenge negative and could be potentially misdiagnosed or overtreated, in turn suggesting the need for supervised step‐down.